Steroid hormone sulphation in lead workers. Issue 3 (March 1989) - Apostoli, P; Romeo, L; Peroni, E; Ferioli, A; Ferrari, S; Pasini, F; Aprili, F
Abstract : The metabolism of steroid hormones has been investigated in 10 workers exposed to lead and in 10 non-exposed subjects to determine whether lead interferes with the first or second phase reactions of steroid hormone biotransformation, or both. In the exposed workers blood lead concentrations (PbB) ranged from 45 to 69 micrograms/100 ml; in the controls PbB was less than 25 micrograms/100 ml. No statistical differences were found for the total amount of the urinary hormone metabolites, but a drop of about 50% was observed for the sulphated portion. It is suggested that lead interferes with the mechanisms of sulphoconjugation through an effect on the cytosol enzymes sulphotransferase and sulphokinase.